Effectiveness of protection program against domestic violence Huánuco - Boza-Quilca, Marleny (2019)
This research was conducted to determine the effectiveness of the "Program protection" against domestic violence in Huánuco. The method developed was intended to deepen the analysis and interpretation of the results of descriptive and inferential way with the kind of applied research field level longitudinal quantitative approach with quasi experimental design with one group and pretest and post test. The sample was composed of 44 women leaders of committees presidents "Glass of Milk" program in 4 áreas: Huánuco, Aparicio Pomares, Blackberries, and rural área, who were applied the survey sector. For statisticians estimate it was made using descriptive statistics and for the testing of the hypothesis Studentt test was applied. We conclude that the "Agenda for Protection against Domestic Violence in Huánuco" has statistically proven its effectiveness in the field of prevention specifically on increasing the level of information, attitudes and initiatives for prevention against any kind of violence domestic.